Case closed. Volume 2 - Aoyama, Gōshō (Viz graphic novel, 2004)
Conan Edogawa, a high school detective mysteriously transformed into a first grader, helps a deceptively sweet girl look for her father, investigates a haunted house, and struggles to solve the murder of a man who has burned to death.